Penerapan Manajemen Kegiatan Santri dalam Meningkatkan Mutu Lulusan Pesantren di Pondok Pesantren Nurul Huda Pragaan Sumenep - Moh Rifki; Rinta Ratnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the implementation of santri activity management in improving the quality of graduates at the Nurul Huda Pragaan Sumenep Islamic Boarding School. The study used a descriptive qualitative approach with a field study method. Data collection techniques were carried out through observation, interviews, and documentation, with data analysis processes in the form of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of educational quality management at the Nurul Huda Islamic Boarding School is carried out through four management functions, namely planning, organizing, implementing, and supervising (POAC). Planning is carried out collaboratively through working meetings with the caretakers and management. Organizing involves the division of tasks and responsibilities based on fields. The implementation of the work program is carried out with the principles of cooperation, continuous evaluation, and determination of quality standards. Meanwhile, supervision is carried out routinely to ensure the sustainability of the program. Supporting factors for the success of implementing quality management include active leadership, community participation, and adequate facilities and infrastructure. Keywords: Graduate Quality, Islamic Boarding School, POAC, Islamic Education